2017
DOI: 10.1038/s41598-017-10404-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GDF8 (Myostatin) accelerates bone regeneration in diabetes mellitus type 2

Abstract: Metabolic diseases like diabetes mellitus cause bone healing deficiencies. We found significant impairment of bone regeneration, osteogenic differentiation and proliferation in diabetic bone. Moreover recent studies suggest a highly underestimated importance of GDF8 (Myostatin) in bone metabolism. Our goal was to analyze the role of GDF8 as a regulator of osteogenic differentiation, proliferation and bone regeneration. We used a murine tibial defect model in diabetic (Leprdb−/−) mice. Myostatin-Inhibitor Folli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 47 publications
1
29
0
2
Order By: Relevance
“…For example, mice grown with FST overexpression via global knock-in exhibited an impaired bone structure (43). However, in adult diabetic mice, FST was shown to accelerate bone regeneration by inhibiting myostatin-induced osteoclastogenesis (44,45). Furthermore, it has been reported that FST down-regulates BMP2-driven osteoclast activation (46).…”
Section: Discussionmentioning
confidence: 99%
“…For example, mice grown with FST overexpression via global knock-in exhibited an impaired bone structure (43). However, in adult diabetic mice, FST was shown to accelerate bone regeneration by inhibiting myostatin-induced osteoclastogenesis (44,45). Furthermore, it has been reported that FST down-regulates BMP2-driven osteoclast activation (46).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the importance of myostatin for bone regeneration has been considered [ 106 ]. Myostatin inhibition restored bone healing in diabetic animals [ 107 ]. Current resear proved that inflammation is a trigger for the interaction of myostatin in musculoskeletal injury.…”
Section: Commonalities and Differences In Healing Cascades Of Diffmentioning
confidence: 99%
“…Myostatin ist ein von Myozyten sekretiertes Molekül der TGF-β-Proteinfamilie und wirkt hauptsächlich als autokriner Inhibitor der Myogenese und Osteogenese [6,7]. Eine Knockout-Mutation dieses Gens zeigt eine deutliche Muskelmassezunahme sowohl im Tier als auch im Menschen [8,9].…”
Section: Elevation Of Myostatin As a Potential Marker For Compartmentunclassified